When school-family relations matter - discomfort and struggle among children, young people and their parents - Dannesboe, Karen Ida; Kryger, Niels; Palludan, Charlotte (International Journal about Parents in Education, 2019)
Ethnographic studies offer insight into parents’ involvement in and management of children’s and young people’s school lives in a Danish context. In light of the growing demand for parental involvement in school, the article explores the emotional work that families’ interactions with the school imply and their attempts to avoid unwanted categorisation or stigmatisation. At the core of the article are three cases drawn from a larger study of home-school relations in Denmark. The three cases present examples of the emotional work involved when children and young people are categorised by the school as ‘students with inappropriate behaviour’. Drawing on Erwin Goffman’s concepts of frontstage, backstage and impression management, the analysis emphasises how these families’ management of their children’s school lives is dominated by time and effort spent dealing with feelings of anxiety and inadequacy. Furthermore, the study shows how parents and children struggle to gain recognition and avoid the school’s categorisation of them.